INNOVATIVE METHODS FOR SHELL SEPARATION IN APRICOT KERNEL PROCESSING (International journal of artificial intelligence, 2026)
This article analyzes innovative methods for shell separation in apricot kernel processing. A comparative study of traditional and modern technologies is conducted, focusing on energy efficiency, product quality, and production performance. In addition, the possibilities of optimizing mechanical and technological parameters of the shell separation process are substantiated. The research findings contribute to improving processing efficiency and promoting rational use of resources in apricot kernel processing.